FGF-2 expression and the amount of fibroblast in the incised wounds of Rattus norvegicus rats induced with Mauli banana (Musa acuminata) stem extract - Didit Aspriyanto; Intan Nirwana; Hendrik Setia Budi (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: Traditional wound treatment using herbal medicine is thought to maintain the health of families and society in general economically, effectively, and efficiently without inducing side effects. One genus of plant that can be used as a traditional medicine is the Mauli banana, indigenous to South Borneo. Mauli banana stem contains bioactive compounds, most of which are tannins along with ascorbic acid, saponin, β-carotene, flavonoids, lycopene, alkaloids, and flavonoids. Tanin has antibacterial and antioxidant effects at low concentrations, as wells as antifungal ones at high concentrations. Purpose: This study aimed to analyze the effects of Mauli banana stem extract at concentrations of 25%, 37.5%, and 50% on the quality of incised wound healing in male Rattus norvegicus rats by assessing FGF-2 expression and fibroblast concentration on days 3 and 7. Methods: This research represented an experimental laboratory-based investigation involving 32 rats of the Rattus norvegicus strain aged 2-2.5 months old. Sampling was performed using a simple random sampling technique since the research population was considered homogeneous and divided into 8 treatment groups (C3, M3-25, M3-37.5, M3-50, C7, M7-25, M7-37.5, M7-50). The rats in each group were anesthetized before their back was incised with length and width of 15x15mm with a depth of 2mm. Gel hydroxy propyl cellulose medium (HPMC) was applied to the incised wound of each rat in the control group, while stem Mauli banana extract was applied to that of each rat in the treatment groups three times a day at an interval of 6-8 hours. On day 3, four rats from each group were sacrificed, while, in the remaining groups, the same procedure was performed until day 7, at which point they (8 groups) were sacrificed for HE examination in order to assess the amount of fibroblast and for IHC examination to examine FGF-2 expression. Data regarding FGF-2 expression and the amount of fibroblast were analysed by means of One-way Anova and HSD. Results: The results showed that the Mauli banana stem extract could significantly improve the expression of FGF-2 and the amount of fibroblast cells compared to C3 and C7 groups. The highest increase in FGF-2 expression and fibroblast amount were found in all groups on days 3 and 7 treated with the Mauli banana stem extract at a concentration of 50%. Conclusion: There was an increase of FGF-2 expression and the amount of fibroblast cells in the incision wound healing process that induced with Mauli banana stem extract.